2006
DOI: 10.1007/s10637-006-7073-4
|View full text |Cite
|
Sign up to set email alerts
|

Studies on reaction of amino acids and triplet thioxanthone derivatives by laser flash photolysis

Abstract: Excitation of the thioxanthone derivatives (TXs), 2, 4-diethylthioxanthone (DETX) and 2-(2,3-epoxypropyloxy) thioxanthone (ETX) in acetonitrile/water mixture solution (1:1, v/v) upon 355 nm laser flash produced the triplet of TXs ((3)TXs(*)). Characteristic absorption spectra of (3)TXs(*)(590 nm) were recorded and rate constants of (3)TXs(*) quenched by O(2) and by its ground state were determined (9.8 x 10(9) M(-1) s(-1), 7.3 x 10(9) M(-1) s(-1) and 2.6 x 10(8) M(-1) s(-1), 2.2 x 10(8) M(-1) s(-1) respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The reduction potential for NAT, E °(NAT •+ /NAT), should not be so different from those reported for tryptophan and some methylindole derivatives, ranging between 1.23 and 0.93 V. These values are in the same E ° range of amines that we previously used to photoreduce 3-phenylquinoxalin-2-one derivatives. , Therefore, it is reasonable to expect a SET from NAT to the substituted quinoxalin-2-one. For NAT derived radicals, transient absorptions are expected near 560 nm for the radical cation NAT •+ and close to 510 nm for the deprotonated neutral radical NAT-H • , similar to those reported for tryptophan radicals. , …”
Section: Introductionsupporting
confidence: 76%
“…The reduction potential for NAT, E °(NAT •+ /NAT), should not be so different from those reported for tryptophan and some methylindole derivatives, ranging between 1.23 and 0.93 V. These values are in the same E ° range of amines that we previously used to photoreduce 3-phenylquinoxalin-2-one derivatives. , Therefore, it is reasonable to expect a SET from NAT to the substituted quinoxalin-2-one. For NAT derived radicals, transient absorptions are expected near 560 nm for the radical cation NAT •+ and close to 510 nm for the deprotonated neutral radical NAT-H • , similar to those reported for tryptophan radicals. , …”
Section: Introductionsupporting
confidence: 76%
“…13 Recently, the photoinduced electron-transfer reactions between the triplet excited state of TX with indolic and phenolic derivatives have been reported. 5,6,14 In most of the TX photochemistry, the long-lived lowest triplet state has been attributed to be responsible for the photosensitization reactions. It has also been shown that the photochemical reaction efficiency and relaxation behavior of carbonyl compounds can be correlated with the electronic state configuration (ππ* or nπ*) of the lowest triplet excited state.…”
Section: ' Introductionmentioning
confidence: 99%
“…ring, 12,17,18 and the chelated Mg 2+ had little influence on the two absorptions at 550 and 700 nm according to the literature. 19 TDBP had a series of weak absorptions in 500-700 nm region.…”
Section: Steady-state Uv-vis Absorptions Of Mg-purpurin-18 M-tcpp Amentioning
confidence: 65%